KETERSEDIAAN FOSFAT, SERAPAN FOSFAT DAN HASIL TANAMAN JAGUNG AKIBAT PEMBERIAN BOKASHI ELA SAGU DENGAN PUPUK FOSFAT PADA INCEPTISOLS - M. La Habi (BUANA SAINS, 2012)
The aim of this research was to determine the P-availability, P-uptake and maize yield due to applied sago pith waste bokashi with phosphate fertilizer on Inceptisols. This research was conducted in the in the greenhouse at the Faculty of Agriculture, Brawijaya University. The experimental design was completely randomzzed factorial design with two factors. The first factor was sago pith waste bokashi and the second factor was phosphate fertilizer (SP-36).The results showed that the sago pith waste bokashi combined with fosfat fertilizer increased soil pH, P availability in soil and dry grains yield of maize, meanwhile the sago pith waste bokashi and fosfat fertilizer individually increased P-uptake of plant. The best dose of the sago pith waste bokashi was 80 t/ha and fosfat fertiizer was 240 kg P/ha effectively increased dry grains yield of maize that was equal to 7,85 t/ha